2015
DOI: 10.1016/j.ccell.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Engineered against a Native Antigen Can Surmount Immunologic and Physical Barriers to Treat Pancreatic Ductal Adenocarcinoma

Abstract: SUMMARY Pancreatic ductal adenocarcinomas (PDA) erect physical barriers to chemotherapy and induce multiple mechanisms of immune suppression, creating a sanctuary for unimpeded growth. We tested the ability of T cells engineered to express an affinity-enhanced T cell receptor (TCR) against a native antigen to overcome these barriers in a genetically engineered model of autochthonous PDA. Engineered T cells preferentially accumulate in PDA and induce tumor cell death and stromal remodeling. However, tumor-infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
226
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(243 citation statements)
references
References 59 publications
16
226
1
Order By: Relevance
“…CAR-T cells have the ability to gain access to the epithelial cell compartment by invading through the ECM and evading immunosuppressive signals 321 . In preclinical studies CAR-T cells have been reprogrammed to recognize FAP-positive cells and target stromal cells specifically 322 .…”
Section: Tumour-stroma Targeting Strategiesmentioning
confidence: 99%
“…CAR-T cells have the ability to gain access to the epithelial cell compartment by invading through the ECM and evading immunosuppressive signals 321 . In preclinical studies CAR-T cells have been reprogrammed to recognize FAP-positive cells and target stromal cells specifically 322 .…”
Section: Tumour-stroma Targeting Strategiesmentioning
confidence: 99%
“…Robust clinical responses have been observed in a number of cancer types such as chronic lymphocytic leukemia and B-cell lymphoma Kochenderfer and Rosenberg 2013). Although TCRs against mesothelin, a native antigen highly expressed in PDAC, exhibited a promising survival benefit in a Kras-driven PDAC GEMM (Stromnes et al 2015), the effectiveness of these engineered T-cell therapies for human tumors remains to be determined. While multiple clinical trials are ongoing to test the safety and anti-tumor effects of various anti-mesothelin-based CARs in PDAC patients (clinical trial information: NCT01583686, NCT02465983, and NCT02580747), a phase I trial in six PDAC patients indicated that it was well tolerated ( Fig.…”
Section: Prospect Of Pdac Immunotherapymentioning
confidence: 99%
“…Recently, it was shown in an elegant study that T cells engineered to express affinity-enhanced TCR can overcome intratumoural immune suppression and induce pancreatic cancer cell death 158. A similar approach is the adoptive transfer of T cells genetically modified to express a chimeric antigen receptor (CAR).…”
Section: Introductionmentioning
confidence: 99%